2021
DOI: 10.1101/2021.01.04.425251
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CcLBD25functions as a key regulator of haustorium development inCuscuta campestris

Abstract: Parasitic plants reduce yield of crops worldwide. Cuscuta campestris is a stem parasite that attaches to its host, using haustoria to extract nutrients and water. We analyzed the transcriptome of six C. campestris tissues and identified a key gene, CcLBD25, as highly expressed in prehaustoria and haustoria. Our gene co-expression networks (GCN) from different tissue types and laser-capture microdissection (LCM) RNA-Seq data indicate that CcLBD25 could be essential for regulating cell wall loosening and organog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…We designed our study to investigate the involvement of wound-induced tissue regeneration during junction formation, and thus this work inherently uncovers genetic hubs that were not previously considered to play a role in grafting. These hubs have, however, been implicated in the related process of haustorium formation in parasitic plants, and thus provide molecular support for the connection between graft junctions and haustoria ( Melnyk et al, 2018 ; Xie et al, 2019 ; Jhu et al, 2021 ). The fact that we identified diverse regulatory hubs between our species, supports a model in which grafting is not controlled by genetically conserved regulatory genes that are evolutionarily programmed into plant genomes.…”
Section: Discussionmentioning
confidence: 99%
“…We designed our study to investigate the involvement of wound-induced tissue regeneration during junction formation, and thus this work inherently uncovers genetic hubs that were not previously considered to play a role in grafting. These hubs have, however, been implicated in the related process of haustorium formation in parasitic plants, and thus provide molecular support for the connection between graft junctions and haustoria ( Melnyk et al, 2018 ; Xie et al, 2019 ; Jhu et al, 2021 ). The fact that we identified diverse regulatory hubs between our species, supports a model in which grafting is not controlled by genetically conserved regulatory genes that are evolutionarily programmed into plant genomes.…”
Section: Discussionmentioning
confidence: 99%
“…The genomes of C. campestris and C. australis were both published in 2018 (Sun et al, 2018;Vogel et al, 2018). The Cuscuta transcriptome profiles in different developmental stages and tissue types are readily available (Ranjan et al, 2014;Jhu et al, 2021;Bawin et al, 2022). Cuscuta mobile mRNAs and miRNAs that can transfer into the host plants are also reported (Kim et al, 2014;Shahid et al, 2018).…”
Section: Advantage 3: Whole Genome and Abundant Transcriptome Data Ar...mentioning
confidence: 99%
“…In addition, as mentioned in previous sections, many studies have shown that far-red light signals and physical contacts can trigger Cuscuta haustorium formation (Furuhashi et al, 1995;Tada et al, 1996;Furuhashi et al, 1997;Haidar and Orr, 1999). Therefore, several in vitro methods of growing Cuscuta or inducing haustorium formation without hosts have also been developed simultaneously (Kaga et al, 2020;Jhu et al, 2021;Bernal-Galeano et al, 2022). These methods allow us to investigate the function of genes in haustorium organogenesis more effectively and remove the influence or variations created by host conditions.…”
Section: Advantage 4: Easy Propagation and In Vitro Haustorium Systemmentioning
confidence: 99%
See 1 more Smart Citation